PENGEMBANGAN USAHA KELOMPOK PERAJIN TEMPE DI KECAMATAN CANDI KABUPATEN SIDOARJO (UPN VETERAN JAWA TIMUR, 2015)
ABSTRACT There are 500 artisans of tempeh in Sepande village, subdistrict Sidoarjo, but it was not incorporated as a member of the Primary Cooperative Producers of Tofu- Tempeh Indonesia (PRIMKOPTI)